6x-2=3x-2

Simple and best practice solution for 6x-2=3x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2=3x-2 equation:


Simplifying
6x + -2 = 3x + -2

Reorder the terms:
-2 + 6x = 3x + -2

Reorder the terms:
-2 + 6x = -2 + 3x

Add '2' to each side of the equation.
-2 + 2 + 6x = -2 + 2 + 3x

Combine like terms: -2 + 2 = 0
0 + 6x = -2 + 2 + 3x
6x = -2 + 2 + 3x

Combine like terms: -2 + 2 = 0
6x = 0 + 3x
6x = 3x

Solving
6x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6x + -3x = 3x + -3x

Combine like terms: 6x + -3x = 3x
3x = 3x + -3x

Combine like terms: 3x + -3x = 0
3x = 0

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| 4(0.4)+(-2)(1-0.4)=x | | (-243x^10y^5)^(4/5) | | 3x+x-7=2x-5x+4 | | 7÷44/5 | | 4p+(-2)(1-p)=(-2)p+2(1-p) | | -3(1-3)=2(-4x+7) | | 10x+21=35-2x | | 4x^2+y^2+2y-3=0 | | 1/3t-4/3=-(5/4)t-3/2 | | x^2+8x-57=6 | | 8k-6=-(1-3k) | | 3(0.3)+(-1)(1-0.3)=x | | 6x-6=-5x+5 | | 3(0.3)+(-1)(1-0.3)= | | 100+20t+3t^2=0 | | 5x-10=6-x | | -3(1-3)+8(x-3)=6x+7-5x | | mx+bformx+5y=-5 | | -50+12=-38 | | 6(3x-6)=50 | | 8+2(-5+9n)=15+n | | 10p-2p-9=39 | | 4(2x-4)=9 | | 3(q)+(-1)(1-q)=(-4)q+2(1-q) | | x-21+x=47 | | P/5-4=6 | | -8w=2 | | 6x+10=6(x+3) | | 6x-12=20+4 | | 9(3y-6)-(8y+3)= | | y=-(4-x)(x+3) | | 6+4w=-2 |

Equations solver categories